A Peasant’s Satire of the Politics of Debt (Luke 16:1–8a) - Guevara, Jonathan (2024)
This article reads the parable of the unjust steward (Luke 16:1–8a) using a social-scientific method, particularly the anthropology of agrarian patron-client relations. Here I delineate a model of the erosion of patron-client bonds, based on the work of James C. Scott and others, and the emergence of horizontal solidarity and mutual aid (“balanced reciprocity”). I relate this model to the peasant’s burden of debt, particularly in Jesus’ world. As commercialization develops in an agrarian society patron-client bonds begin to erode, and peasants begin to understand these bonds as relations of exploitation. Consequently, subversive ideology develops, evident in peasant folktales directed against the wealthy and powerful. Accordingly, I argue that the parable of the unjust steward is a satire aimed at landlord-patrons who perpetuate the burden of debt.
Keywords: Peasants; Satire; Patronage; Social-scientific; Luke 16:1–8a; Debt; Unjust Steward